Biofilms and chronic wounds: winning the war in wounds - Schultz, Gregory (Henry Stewart Talks, 2014)
Sequence of Molecular and Cellular Events in Skin Wound Healing, Hypothesis of Chronic Wound Pathophysiology, Bacterial Biofilms, Damage caused by immune response to biofilms, Role of matrix metalloproteinases in wound healing, Why are biofilms difficult to kill?, Can Dressings Disrupt & Kill Mature Biofilms?, Larval Debridement Therapy, Negative Pressure Wound Therapy
Reviewed at 2022/10/11